2007
DOI: 10.1128/iai.00153-07
|View full text |Cite
|
Sign up to set email alerts
|

Slc11a1, Formerly Nramp1, Is Expressed in Dendritic Cells and Influences Major Histocompatibility Complex Class II Expression and Antigen-Presenting Cell Function

Abstract: Solute carrier family 11 member a1 (Slc11a1; formerly Nramp1) encodes a late endosomal/lysosomal protein/ divalent cation transporter that regulates iron homeostasis in macrophages. During macrophage activation, Slc11a1 has multiple pleiotropic effects on gene regulation and function, including gamma interferon-induced class II expression and antigen-presenting cell function. The wild-type allele at Slc11a1 has been associated with a bias in Th1 cell function in vivo, which is beneficial in resistance to infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 49 publications
2
65
0
3
Order By: Relevance
“…The protein structural characteristics of Slc11a1, i.e., 12-transmembrane domains and a transport motif, indicate a function as an ion channel and a transporter (5,8). Intracellular staining of Slc11a1 in macrophages and dendritic cells demonstrated that the protein is restricted to intravacuolar compartments, especially late endosomes and lysosomes (7,9,10). A glycine to aspartic acid substitution at position 169 (G169D) within the fourth transmembrane domain of Slc11a1 is present in many mouse strains and reduces Slc11a1 expression on the phagosomal membrane (11,12).…”
Section: Conclusion-the Association Of Variants Encoding Slc11a1mentioning
confidence: 99%
See 1 more Smart Citation
“…The protein structural characteristics of Slc11a1, i.e., 12-transmembrane domains and a transport motif, indicate a function as an ion channel and a transporter (5,8). Intracellular staining of Slc11a1 in macrophages and dendritic cells demonstrated that the protein is restricted to intravacuolar compartments, especially late endosomes and lysosomes (7,9,10). A glycine to aspartic acid substitution at position 169 (G169D) within the fourth transmembrane domain of Slc11a1 is present in many mouse strains and reduces Slc11a1 expression on the phagosomal membrane (11,12).…”
Section: Conclusion-the Association Of Variants Encoding Slc11a1mentioning
confidence: 99%
“…Slc11a1 has been characterized primarily for its ability to mediate resistance to intracellular pathogens such as Salmonella and Leishmania via its expression in macrophages (5,6). Moreover, recently, Slc11a1 was shown to be expressed in dendritic cells (7). The protein structural characteristics of Slc11a1, i.e., 12-transmembrane domains and a transport motif, indicate a function as an ion channel and a transporter (5,8).…”
Section: Conclusion-the Association Of Variants Encoding Slc11a1mentioning
confidence: 99%
“…EGTA sensitivity and divalent cation stress phenotypes in yeast expressing Slc11a orthologues show that symport activity is ancestral. Molecular changes that mediate rescue of the divalent cation stress phenotype post-date frogs and co-evolved with Slc11a1 orthologues that regulate divalent cation homeostasis in macrophages and resistance to infection in chickens and mammals.Slc11a1 (formerly Ity/Lsh/Bcg/Nramp1) is a proton/divalent cation transporter with 12 putative transmembrane domains (TMD) 4 (1) that localizes to late endosomes and lysosomes of macrophages (2, 3) and dendritic cells (4), and tertiary granules of neutrophils (5). It is recruited to phagosome membranes in macrophages infected with Mycobacterium (2, 3) or Leishmania (3), and regulates cellular divalent cation homeostasis (6, 7).…”
mentioning
confidence: 99%
“…Slc11a1 (formerly Ity/Lsh/Bcg/Nramp1) is a proton/divalent cation transporter with 12 putative transmembrane domains (TMD) 4 (1) that localizes to late endosomes and lysosomes of macrophages (2, 3) and dendritic cells (4), and tertiary granules of neutrophils (5). It is recruited to phagosome membranes in macrophages infected with Mycobacterium (2, 3) or Leishmania (3), and regulates cellular divalent cation homeostasis (6, 7).…”
mentioning
confidence: 99%
“…Além disso, interage na produção de IFN-γ e IL-1 (KITA et al, 1992;RAMARATHINAM et al, 1993), e na expressão de moléculas do complexo principal de histocompatibilidade (LANG et al, 1997;WOJCIECHOWSKI et al, 1999;STOBER et al, 2007).…”
Section: Seleção De Genética Bidirecional De Linhagens De Camundongosunclassified